Sex differences and gender-oriented characteristics in intensive care unit admissions for patients with traumatic brain injury in Spain - Cruz-Garcinuño, Manuel; Juárez-Vela, Raúl; Chover-Sierra, Elena; Navas-Echazarreta, Noelia; Czapla, Michal; Ballestar-Tarín, María Luisa; Martínez-Pascual, Raquel-María; Nanwani-Nanwani, Kapil; Serrano-Lazaro, Ainhoa; del Val-Rey, Ismael; Quintana-Díaz, Manuel; Martinez-Sabater, Antonio (Frontiers in Medicine, 2025)
BackgroundTraumatic brain injury (TBI) is a major public health concern with significant mortality, disability, and socioeconomic impact. Previous studies have shown that biological sex influences TBI incidence and outcomes, yet sex-specific data remain underexplored. We aimed to analyze clinical characteristics, resource utilization, and outcomes of ICU-admitted TBI patients in Spain, with a focus on sex-related differences.Material and methodsWe performed an observational and retrospective study utilizing data from the RETRAUCI registry, involving 50 registered ICUs and 124 investigators. Patients admitted from March 2015 to December 2019 with isolated significant TBI (AIS ≥ 3) were included. Data on epidemiology, acute management, injury type, resource utilization, complications, and outcomes were recorded.ResultsOf the 950 patients, 76% were male. Women had significantly longer ICU stays (11.03 vs. 9.43 days; p = 0.026), and a higher rate of chronic psychotropic drug use. Men were more frequently involved in traffic accidents and had higher rates of alcohol (23.2% vs. 9.3%; p < 0.001) and drug use (11.4% vs. 5.3%; p = 0.007). No significant sex differences were found in complication rates, neuromonitoring, or mortality.ConclusionThese findings show that sex significantly influences TBI patterns and in-hospital evolution. Men had higher rates of trauma from risk-related behaviors, while women experienced longer ICU stays and greater psychotropic use. Such differences call for sex-specific approaches in clinical care and further prospective research.